Adverse childhood experiences: association with physical and mental health conditions among older adults in Bhutan. (May 2020) - Dorji, N.; Dunne, M.; Deb, S.
Abstract: Objectives: Adverse childhood experiences (ACEs) are events stressful, traumatic, and related to the development of a wide range of health conditions throughout the person's lifespan. This study explored the relationship between ACEs and health conditions among older adults in Bhutan. Study design: Cross-sectional survey. Methods: Older adults aged 60–101 years ( n = 337) completed a face-to-face interview in a convenient community setting in the four major towns of Bhutan. Measurements included the modified World Health Organization Adverse Childhood Experiences International Questionnaire and the checklist of chronic health conditions. Results: Commonest ACEs reported by the sample were related to the contribution of physical labour in childhood (n = 284 [84.3%]) and witnessing of community violence (n = 185 [54.9%]). Assuming an adult role while still a child highly co-occur with other forms of ACEs. Compared to 0–2 ACEs, participants with ≥7 ACEs had the higher odds of reporting lung disease (odds ratio [OR] = 2.15, 95% confidence interval [CI]: 1.03–4.49), visual impairment (OR = 2.38, 95%CI: 1.16–4.85), insomnia (OR = 2.35, 95%CI: 1.11–4.98), and memory decline (OR = 2.30, 95%CI: 1.10–4.78) by twofold and high blood pressure by threefold (OR = 3.21, 95%CI: 1.39–7.38). Overall, the odds of self-rated poor health conditions among those ≥7 ACEs compared to 0–2 ACEs was high by almost twofold (OR = 1.97; 95%CI: 1.04–3.73). Conclusions: The influence of ACEs on health conditions persisted into late adulthood, and older people in Bhutan have had a complex variety of chronic health conditions implicating greater demand on the free healthcare system in Bhutan. ACEs prevention is critical to promote better health for a country like Bhutan, where the healthcare services are provided free of cost to its citizens. Highlights: ACEs are traumatic events that have an effect on the biopsychosocial health across the lifespan of a person. Compared to individual with 0–2 ACEs, those ≥7 ACEs had the higher odds of reporting lung disease, visual impairment, insomnia, and memory decline by two folds including self-rate poor health conditions. Assuming an adult role while still a child highly co-occur with other forms of ACES. ACEs prevention is critical to promote better health for a country like Bhutan, where the healthcare services are provided free of cost to its citizens.